Arresting environmental degradation through accelerated on-site soil sedimentation and revegetation using microcatchments and reseeding - Mnene, W.N.; Wandera, F.P.; Lebbie, S.H.B. (Kenya Agricultural Research Institute, 1999)
Degradation of arid and semi-arid lands (ASALs) through denudation has been found to result in lowered capacity to support livestock, particularly under extensive production systems. After a participatory rural appraisal (PRA) in Kajiado district, an opportunity was identified in the pastoral reserve grazing areas involving the combined use of microcatchments (specifically pitting) and reseeding with adapted forage species. Treatments were imposed before the 1996 short rainy season. Data were collected on soil sedimentation as well as herbaceous cover and standing crop. Much of the soil deposit comprised of fine silt/clay in the pits and sand on the up-slope. No soil deposit was observed on the down-slope of the pits. This increased in subsequent rainfall seasons. Although seeding was done by broadcasting to cover whole plots, establishment was only evident where it was pitted. Volunteer herbaceous vegetation expressed themselves and plant cover tended to also increase in freshly deposited soil form one wet season to another. Herbage was particularly dense on the crescents of the pits.